2001
DOI: 10.1038/sj.bmt.1703253
|View full text |Cite
|
Sign up to set email alerts
|

Allogeneic transplantation for multiple myeloma: further evidence for a GVHD-associated graft-versus-myeloma effect

Abstract: Summary:We report a series of 37 consecutive patients with multiple myeloma (MM) who received an allograft between 1990 and 2000 at our institution. Median age was 47 years, and nearly 70% of patients were Durie-Salmon stage III. A median of five cycles of chemotherapy were given before transplant, with a median interval between diagnosis and transplant of 9.3 months. We report a nonrelapse mortality rate of 22% with a median followup period of 40 months, whereas complete remission (CR) rate at 12 months is es… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
38
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 66 publications
(45 citation statements)
references
References 35 publications
7
38
0
Order By: Relevance
“…[7][8][9] Factors associated with improved PFS included fewer treatments before transplant, grade I acute GvHD and presence of chronic GvHD. This protective effect of chronic GvHD, [10][11][12][13][14] response after donor lymphocyte infusion 15,16 and the discovery of antibodies against highly expressed myeloma-associated Ags 17 following allogeneic transplant are additional clinical observations supporting the existence of a graft-versus-myeloma (GvMM) effect.…”
Section: Introductionmentioning
confidence: 98%
See 2 more Smart Citations
“…[7][8][9] Factors associated with improved PFS included fewer treatments before transplant, grade I acute GvHD and presence of chronic GvHD. This protective effect of chronic GvHD, [10][11][12][13][14] response after donor lymphocyte infusion 15,16 and the discovery of antibodies against highly expressed myeloma-associated Ags 17 following allogeneic transplant are additional clinical observations supporting the existence of a graft-versus-myeloma (GvMM) effect.…”
Section: Introductionmentioning
confidence: 98%
“…Recently, allogeneic HSCT has received less enthusiasm due to prohibitive (20-30%) non-relapse mortality (NRM) associated with myeloablative conditioning 11 and high relapse rates (50-70%), following non-myeloablative (NMA) transplant. 18 Several controlled trials comparing autologous transplant alone to a tandem approach have questioned the survival benefits of NMA allogeneic HSCT for newly diagnosed MM patients, leading to conflicting results.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A small retrospective report of 37 patients who received conventional allografts for multiple myeloma found that among 15 patients who achieved complete response, 11 had chronic GVHD while four did not. [6] Individual case reports have documented a graftversus-myeloma effect in association with GVHD when immunosuppression was withdrawn. [7] Small series of patients with multiple myeloma who developed post-allograft relapses and who subsequently were infused with allogeneic leukocytes from their original stem-cell donors have clearly demonstrated a graft-versus-myeloma effect that was associated with GVHD.…”
Section: Graft Versus Myelomamentioning
confidence: 99%
“…Although cGVHD is associated with a graft-versus-myeloma effect preventing relapse after alloHSCT, 6 relapses with extramedullary manifestations appear to occur more frequently due to altered biology and local immunological escape effects. 7,8 Furthermore, malignant plasma cells may have survived in the fatty tissue of the orbit, potentially providing a sanctuary for persistence of malignant cells.…”
mentioning
confidence: 99%